Gestión de personal y su incidencia en la tasa de rotación laboral del Consorcio Latino de Actividades Comerciales ciudad de Lima, año 2018 - Cueva Masías, Nanina Linett (2019)
The following research work aims to determine the incidence of personnel management in the labor turnover rate of the Consorcio Latino de Actividades Comerciales, Lima, Year 2018; for which it was required to know the current situation of the company in the area of human resources. Then, in order to gather the necessary information, a structured survey of the collaborators was used. The problem formulated in this research thesis is: How does personnel management affect the labor turnover rate of the Consorcio Latino de Actividades Comerciales, Lima, Year 2018?, for which the hypothesis that Personnel management directly affects the labor turnover rate. The universe studied for the present work is constituted by 358 employees of the company, of which 60 individuals were taken as a sample applying the specified statistical formula. The research method used in this thesis is the deductive-inductive, with a causal correlational transactional design, and was applied as a data collection technique to the survey, as well as the questionnaire as an instrument. The general conclusion reached was that personnel management inversely affects the labor turnover of the Latin Consortium of Commercial Activities, this depending on the theoretical framework and the results obtained.